Pelatihan Kader dalam Rangka Peningkatan Program Posyandu Remaja di Dadapan Kelurahan Sendangmulyo Kecamatan Tembalang Kota Semarang - Nurjanah, Siti; Puspitaningrum, Dewi; Mustika, Dian Nintyasari (Universitas Muhammadiyah Semarang, 2023)
The problem of youth health is so complexity because they are in a periode of change from a child to an adult. If it is not solved so it will have an effect for the future and psychology. In Permenkes no 25, 2014 as Health policy showed that every youth had a skill to behave clean and healthy life and also socialize well in order to learn as well as grow optimally and become human resource qualitatively. One of the effort to alleviate the problem of youth is by forming an organization for youth that is named by Youth Integrated Healthcare Center (Posyandu Remaja). It has some activities such as counselling, sharing about health-acknowledgment. Youth Integrated Healthcare Center is a solution in social-community to increse the wealth and youth reproduction health. The purpose of community servicing is to training youth Integrated Healthcare Center and grow Youth Integrated Healthcare Center’s acknowledgement. The methode is Cadre training of Youth Integrated Healthcare Center, then giving education, discoursing, discussion and practicing to the cadre of youth Integrated Healthcare Center. The result of this activity is the increasing of cadre’s youth Integrated Healthcare center acknowledgement and the continuing youth Integrated Healthcare center’s activity at Dadapan Sendangmulyo. The conclusion of this activity is able to increse youth health at Dadapan Sendangmulyo on Tembalang in Semarang.